Navigating investment decisions with social connectedness: Implications for venture capital - Nguyen, Giang; Nguyen, My; Pham, Anh Viet; Pham, Man Duy (Marty) (Journal of Banking & Finance, 2023)
This study examines how the geographical structure of social networks shapes venture capital (VC) investment decisions. We find that VC firms invest more in portfolio companies in socially connected regions. The effect is more pronounced among independent, smaller, less reputable, early–stage–focused VC firms and those not from a VC hub. We further document that social connectedness lowers the likelihood of a successful exit since it induces VC firms to undertake suboptimal investment decisions. Overall, our findings highlight the role of social connectedness in constituting the geographical differences in VC firms’ capital allocation and investment outcomes.